Monetary valuations of university course delivery: the case for face-to-face learning activities in accounting education - Taplin, Ross; Kerr, Rosie; Brown, Alistair (2017)
Student preferences for delivery options were obtained within a monetary framework by asking students to purchase their ideal course structure. Results show that accounting students prefer to spend more on tutorials but purchase less lecture time; the difference due to the higher cost of tutorials compared to lectures. Face-to-face classes were preferred to web-based materials. Within lectures and tutorials students prefer more time devoted to teacher-centred activities than student-centred activities. Monetary valuations, where students must take into account the cost of delivery as well as effectiveness, provide insights for teaching staff and administrators, who need to simultaneously enhance teaching and learning, satisfy student preferences and operate with limited resources. Online and/or student-centred learning may not be compatible with preferences of accounting students. Teachers need to balance calls to change educational delivery and learning activities with preferences of accounting students, or ensure they educate students on why non-preferred approaches are undertaken.